2012
DOI: 10.1044/1092-4388(2011/11-0075)
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sampling Context on Spontaneous Expressive Language in Males With Fragile X Syndrome or Down Syndrome

Abstract: Purpose This study examined the impact of sampling context on multiple aspects of expressive language in males with fragile X syndrome in comparison to males with Down syndrome or typical development. Method Participants with fragile X syndrome (n = 27), ages 10 to 17 years, were matched groupwise on nonverbal mental age to adolescents with Down syndrome (n = 15) and typically developing 3- to 6-year-olds (n = 15). Language sampling contexts were an interview-style conversation and narration of a wordless bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(144 citation statements)
references
References 61 publications
8
127
1
8
Order By: Relevance
“…Kover, McDuffie, Abbeduto, & Brown, 2012). Variability due to C-units versus total utterances did not appear to be an issue, because children seldom used simple compound sentences that could inflate MLU (Abbeduto, Benson, Short, & Dolish, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kover, McDuffie, Abbeduto, & Brown, 2012). Variability due to C-units versus total utterances did not appear to be an issue, because children seldom used simple compound sentences that could inflate MLU (Abbeduto, Benson, Short, & Dolish, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the contexts used for language sampling may have limited the opportunities for children with FXS to produce advanced syntactic structures. It has been suggested that "sampling contexts vary in the extent to which they elicit the upper bound of an individual's linguistic ability" (Kover et al, 2012(Kover et al, , p. 1023. The contexts we sampled (e.g., conversation, free play) between the child and an adult might not support the production of complex syntactic structures.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…With the aim to verify the linguistic development, especially the morphosyntactic, we chose to compare the subjects' initial and final performances by assessing samples of natural spontaneous speech in an interaction situation of symbolic play, as indicated in literature 12,28,30 . To assure such performance, the adolescents were assessed in dyads with their respective caregivers.…”
Section: Resultsmentioning
confidence: 99%
“…Not all of these studies are conducted with a numerous or homogeneous population, when considering the chronological age; moreover, the therapeutic procedures used in morphosyntax intervention are frequently not informed 3,9,12,14,28 .…”
Section: Discussionmentioning
confidence: 99%
“…The goal has been to identify a measure of lexical diversity that is effective, yet minutely affected by language sample length. Studies have been conducted in various languages including English (Owen & Leonard, 2002;Heilmann, Nockerts & Miller, 2010;McCarthy & Jarvis, 2010;Kover et al, 2012;Fergadiotis, Wright & Green, 2015), Cantonese (Klee et al, 2004;Wong et al, 2010), Chinese-English bilinguals (Ooi & Wong, 2012) and Spanish-English bilinguals (Simon-Cereijido & Gutierrez-Clellen, 2009;Bedore et al, 2010). Unfortunately, not all of these studies used the same measure of lexical diversity indices or sample demographic.…”
Section: Introductionmentioning
confidence: 99%